Energy harvesting from electromagnetic interference induced in the human body. Issue 22 (11th October 2016) - Hyoung, C.H.; Hwang, J.H.; Lee, J.H.; Kang, S.W.; Kim, Y.T.
Abstract : Energy harvesting using the human body as an antenna is presented. Low‐frequency interference, mainly in the 40–60 kHz range, was generated from electronic ballast of a fluorescent light. Radiated electromagnetic energy was induced in a human body and a rectifier circuit converted induced energy into DC power. An input matching network of the diode rectifier was designed based on an equivalent source model of interference. A wristband‐type harvesting module comprising a metal electrode designed to be in contact with the human skin was implemented. A power of −8.5 dBm was harvested from the body of a person with a height of 180 cm made to stand 60 cm below a fluorescent light with two 32 W lamps in a hemi‐anechoic chamber. The proposed system can supply energy to the sensors used in body area networks.